A CS1-NKG2D Bispecific Antibody Collectively Activates Cytolytic Immune Cells against Multiple Myeloma - Wing Keung Chan; Siwen Kang; Youssef Youssef; Erin N. Glankler; Emma R. Barrett; Alex M. Carter; Elshafa H. Ahmed; Aman Prasad; Luxi Chen; Jianying Zhang; Don M. Benson; Michael A. Caligiuri; et al. (2018)
Abstract Multiple myeloma (MM) is an incurable hematologic malignancy of plasma cells, with an estimated 30,000 new cases diagnosed each year in the United States, signifying the need for new therapeutic approaches. We hypothesized that targeting MM using a bispecific antibody (biAb) to simultaneously engage both innate and adaptive cytolytic immune cells could present potent antitumor activity. We engineered a biAb by fusing an anti-CS1 single-chain variable fragment (scFv) and an anti-NKG2D scFv (CS1-NKG2D biAb). Although NKG2D is a potent activation receptor ubiquitously expressed on mostly cytolytic immune cells including NK cells, CD8+ T cells, γδ T cells, and NKT cells, the CS1 tumor-associated antigen on MM represents a promising target. CS1-NKG2D biAb engaged human MM cell lines and NKG2D+ immune cells, forming immune synapses. In effector cells, CS1-NKG2D biAb triggered the phosphorylation of AKT, a downstream protein kinase of the activated NKG2D–DAP10 complex. The EC50 values of CS1-NKG2D biAb for CS1high and for CS1low MM cell lines with effector PBMCs were 10−12 and 10−9 mol/L, respectively. CS1-NKG2D biAb acted through multiple types of immune cells, and this induced cytotoxicity was both CS1- and NKG2D-specific. In vivo, survival was significantly prolonged using CS1-NKG2D biAb in a xenograft NOD-SCIDIL2γc−/− (NSG) mouse model engrafted with both human PBMCs and MM cell lines. Collectively, we demonstrated that the CS1-NKG2D biAb facilitated an enhanced immune synapse between CS1+ MM cells and NKG2D+ cytolytic innate and antigen-specific effector cells, which, in turn, activated these immune cells for improved clearance of MM. Cancer Immunol Res; 6(7); 776–87. ©2018 AACR.